(untitled) (Revista Lusófona de Educação, 2025)
This article discusses the relationship between Teaching and Learning about the Holocaust (TLH) and Global Citizenship Education (GCE), the development of school-based TLH in Scotland, and the impact of turbulent international contexts on teachers who teach the Holocaust. These contexts include the Israel-Hamas War (2023-2025). Using evidence from Scotland, where teaching the Holocaust is not mandatory in the curriculum, this article highlights the importance of a whole-school approach where TLH and GCE are seamlessly integrated, and where networking and clear leadership are common practices in school-based TLH. The article also explores the challenges teachers face when delivering TLH and our findings would suggest that despite a turbulent educational context, teachers’ commitment to TLH remains consistent. Keywords: Global Citizenship Education, Holocaust education, teaching and learning about the Holocaust